2007
DOI: 10.1186/1471-213x-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Low concentrations of transforming growth factor-beta-1 induce tubulogenesis in cultured mammary epithelial cells

Abstract: Background: Formation of branching tubes is a fundamental step in the development of glandular organs. To identify extracellular cues that orchestrate epithelial tubulogenesis, we employed an in vitro assay in which EpH4-J3B1A mammary epithelial cells form spheroidal cysts when grown in collagen gels under serum-free conditions, but form branching tubules in the presence of fetal calf serum (FCS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 96 publications
1
13
0
Order By: Relevance
“…J3B1A cells show slightly larger dimensions and have a more squamous cell aspect (Soulié et al, 2014). They usually form spheroidal cysts as well, but exhibit branching tubules in the presence of low concentrations of transforming growth factor beta (Montesano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…J3B1A cells show slightly larger dimensions and have a more squamous cell aspect (Soulié et al, 2014). They usually form spheroidal cysts as well, but exhibit branching tubules in the presence of low concentrations of transforming growth factor beta (Montesano et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of p38α disrupts branching of cultured embryonic lungs [69] and treatment with the pharmacological inhibitor SB203580 blocks growth of cultured embryonic kidneys [70] and tubulogenesis of collecting duct epithelial cells [71, 72]. One group has also reported that TGFβ induces branching morphogenesis of mammary epithelial cells in culture through p38 MAPK [73]; it is important to note that the concentrations of TGFβ used in that study (100-500 pg/ml) are 5-25-fold higher than those used here, and in our hands lead to massive apoptosis of mammary epithelial cells under all culture conditions tested (data not shown). Whether p38 MAPK plays a role in the inhibition of mammary branching by TGFβ in vivo will require further testing and the generation of targeted deletions or conditional mutants.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TGF-β has been described as a tubulogen in a 3D model of mammary tubulogenesis, where TGF-β concentrations of 20 pg/ml to 100 pg/ml induce mammary tubulogenesis in vitro [11]. However, tubulogenesis is increasingly disturbed if TGF-β concentrations are greater than 200 pg/ml [11].…”
Section: Commentarymentioning
confidence: 99%
“…Indeed, TGF-β has been described as a tubulogen in a 3D model of mammary tubulogenesis, where TGF-β concentrations of 20 pg/ml to 100 pg/ml induce mammary tubulogenesis in vitro [11]. However, tubulogenesis is increasingly disturbed if TGF-β concentrations are greater than 200 pg/ml [11]. At 200–500 pg/ml TGF-β pointed outgrowths that lack a visible lumen are observed, and concentrations greater than 500 pg/ml lead to disorganized, lumen-less cell aggregates from which streaks of cells grow into the surrounding matrix.…”
Section: Commentarymentioning
confidence: 99%